Acute myeloid leukemia or myelodysplastic syndrome with chromosome 17 abnormalities and long-term outcomes with or without hematopoietic stem cell transplantation. (August 2020) - Britt, Alec; Mohyuddin, Ghulam Rehman; McClune, Brian; Singh, Anurag; Lin, Tara; Ganguly, Siddhartha; Abhyankar, Sunil; Shune, Leyla; McGuirk, Joseph; Skikne, Barry; Godwin, Andrew; Pessetto, Ziyan; et al.
Highlights: Chromosome 17 abnormalities have poor outcomes in acute myeloid leukemia. Presence of TP53 abnormalities further portends a poor prognosis. Outcomes remain poor despite use of allogenic stem cell transplant. Better depth of remission prior to transplant and new therapies are needed. Abstract: Introduction: Chromosome 17 abnormalities, especially disorders of the 17p region and including TP53 gene mutations, result in very low rates of cure for patients with acute myeloid leukemia (AML) or myelodysplastic syndrome (MDS) treated with conventional chemotherapy or allogeneic hematopoietic cell transplant (allo-HCT). Our retrospective study analyzed outcomes in patients with chromosome 17 (ch17) abnormalities who received conventional chemotherapy followed by allo-HCT versus those who did not receive a transplant. We analyzed whether poor outcomes extend to patients with all types of ch17 abnormalities and the impact of concomitant TP53 gene mutations assessed by next-generation sequencing (NGS) on prognosis. Methods: We retrospectively analyzed diagnostic and outcome data on 98 patients treated at our institution from 2012 to 2018 with AML or MDS who possessed ch17 abnormalities by cytogenetic analysis. The presence of TP53 mutations was analyzed by NGS. Primary endpoint of our study was overall survival (OS). Results: 61 patients with AML and 37 with MDS were included. Complete remission (CR) with first line treatment was similar between induction chemotherapy or hypomethylating agents (HMA), 22.9 % versus 21.6 % (p = 0.33). Median OS for all patients (with or without transplant) was 10 months. Patients with abnormal ch17 in conjunction with any TP53 mutation(s) exhibited worse OS compared to patients without a TP53 mutation (10 versus 23 months, p = 0.02). 30 patients (19 AML, 11 MDS) underwent HCT, with a median OS of 11 months. For AML patients who underwent allo-HCT, 18 were in CR (13 with cytogenetic remission) and 1 had persistent disease at transplant. In the MDS cohort, 3 patients were in CR (2 with cytogenetic remission) and 8 had stable disease. Post allo-HCT survival of AML and MDS cohorts did not differ (p = 0.6), although cytogenetic CR at time of HCT trended towards improved OS (17 versus 8 months; p = 0.6). Conclusions: AML/MDS patients with ch17 abnormalities have poor outcomes with or without HCT. Our results show that patients with ch17 abnormalities and TP53 mutations have a significantly poorer survival compared to patients who have ch17 abnormalities but no TP53 mutations. Drugs targeting abnormalities of the p53 pathway, improvement in depth of response prior to HCT, and novel maintenance strategies are needed for improved outcomes in these patients.